2009
DOI: 10.1073/pnas.0901870106
|View full text |Cite
|
Sign up to set email alerts
|

Intimate bacterial–fungal interaction triggers biosynthesis of archetypal polyketides in Aspergillus nidulans

Abstract: Fungi produce numerous low molecular weight molecules endowed with a multitude of biological activities. However, mining the fullgenome sequences of fungi indicates that their potential to produce secondary metabolites is greatly underestimated. Because most of the biosynthesis gene clusters are silent under laboratory conditions, one of the major challenges is to understand the physiological conditions under which these genes are activated. Thus, we cocultivated the important model fungus Aspergillus nidulans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
556
4
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 596 publications
(581 citation statements)
references
References 34 publications
(31 reference statements)
18
556
4
3
Order By: Relevance
“…For sterigmatocystin and terrequinone production experiments, experimental cultures were grown at 37°C for 72 h. Samples for RNA isolation were taken after 3 h and 48 h. Cross-linking for ChIP experiments was carried out at the same time points. For coincubation experiments, freshly prepared S. rapamycinicus was added to an A. nidulans culture, as described in Schroeckh et al (13). If required, SAHA (4 mM) and anacardic acid (100 μM) were added at the same time point.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For sterigmatocystin and terrequinone production experiments, experimental cultures were grown at 37°C for 72 h. Samples for RNA isolation were taken after 3 h and 48 h. Cross-linking for ChIP experiments was carried out at the same time points. For coincubation experiments, freshly prepared S. rapamycinicus was added to an A. nidulans culture, as described in Schroeckh et al (13). If required, SAHA (4 mM) and anacardic acid (100 μM) were added at the same time point.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of chromosomal DNA and of total RNA of A. nidulans, Northern and Southern blot analysis, and quantitative RT-PCR (qRT-PCR) were performed as described in Schroeckh et al (13). Oligonucleotides are listed in Table S3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biologically, however, an early experiment demonstrated that 14 C-labeled orsellinic acid (OA) (2) could be converted to bibenzoquinone oosporein in B. bassiana cultures (8). It is now clear that OA can be biosynthesized by PKSs in bacteria (21) and fungi (22)(23)(24). These findings suggest that oosporein may be biosynthesized through OA by a PKS gene cluster in Beauveria.…”
mentioning
confidence: 98%
“…[10][11][12][13] Furthermore, it was shown that the intimate contact between A. nidulans and a soil-dwelling actinomycete may lead to the specific induction of a cryptic polyketide gene cluster. 14 These strategies resulted in the discovery of a set of novel secondary metabolites, which could not be located by classical screening methods. Another option often preceding genomic approaches is the systematic investigation of the microbial secondary metabolome under various growth conditions.…”
mentioning
confidence: 99%